Relationships between Attentional Bias and craving in Alcohol Use Disorder: Role of metacognitions. (June 2021) - Delonca, Damien; Trouillet, Raphaël; Alarcon, Régis; Nalpas, Bertrand; Perney, Pascal
Highlights: The relationship between craving and attentional bias is controversial. Metacognitions moderate the effect of exposure to pictures of alcohol on craving. Although attentional bias predicts craving, the effect is spurious. Abstract: Researchers have claimed that craving and Attentional Bias (AB) towards alcohol-related cues can be explained by a common incentive-salience mechanism. However, the exact relationship between AB and craving is a matter of debate. The aim of this study was to show that metacognitions moderate the effect of AB on craving. A sample of 38 alcohol abusers undergoing post-withdrawal treating in a hospital setting completed the visual Dot Probe Detection Task (DPDT), while both pre- and post-task measures of craving were recorded. Our results confirmed significant effects of both exposure to pictures of alcohol, and metacognitions, on craving; in particular, the interaction Metacognition * DPDT was significant. Although we initially confirmed a significant main effect of AB on craving, it became non-significant when adjusted for inter-subject variance, and metacognitions. The effect of the interaction AB * Metacognition on craving was not significant. Our findings support the hypothesis that craving and AB share variance, but the relationship appears to be spurious, and caused by confounding factors. We discuss these results with reference to the metacognitive model of addiction.